Grammatical case in the text of Revelation 4 and 5 - S. J. P. K. Riekert (Acta Theologica)
It is generally assumed that the Greek case system does not function in the usual way in the book of Revelation. Using the distinction between abstract Case and morpho-phonological case one can reconsider the use of case in Revelation in the light of the development in case markings, including new morpho-phonological realisations of certain participles.